Effect of Maternal Nutrition Education on Knowledge, Attitude, and Practice Related to Infant and Toddler Feeding - Nur Mukhlishoh Majidah; Sulistiyawati Sulistiyawati; Bunga Astria Paramashanti (Nutri-Sains: Jurnal Gizi, Pangan dan Aplikasinya, 2021)
This study aims to analyze the influence of maternal nutrition education on knowledge, attitude, and practice of infant and toddler feeding in a community feeding center in Sedayu Subdistrict, Bantul District, Yogyakarta. A quasi-experimental with pre- and posttest control group design was used in this study. Thirty-eight mothers were selected using total sampling in the community feeding center, which control group were chosen by matching the wasting status of their children. Mothers from intervention group were provided with nutrition education, while control group only received regular Posyandu(Pos pelayanan terpadu) programs. Mann-Whitney U test and Wilcoxon Signed Rank test were performed at a 5% level of significance. There was a significant improvement in mothers’ knowledge after receiving nutrition education. The difference elevation scores were shown between the intervention (85.25+14.67) and control (72.98+14.67) with p value=0.016; between pre-intervention (59.99+8.60) and post-intervention (85.25+14.67) groups (p0.001). However, maternal attitudes and practices related to infant and toddler feeding did not affect nutrition education. Maternal knowledge is the only outcome that is significantly affected by nutrition education.  Penelitian ini bertujuan untuk menganalisis pengaruh edukasi gizi pada ibu terhadap pengetahuan, sikap, dan praktik pemberian makan pada bayi dan anak di community feeding center di Kecamatan Sedayu, Kabupaten Bantul, Yogyakarta. Penelitian quasi-experimental ini menggunakan kelompok kontrol pre- dan posttest. Sebanyak 38 ibu dipilih menggunakan teknik total sampling di community feeding center dimana kontrol diambil dengan matching status wasting anak di posyandu. Ibu pada kelompok intervensi diberikan edukasi gizi sementara kontrol hanya menerima program regular di posyandu. Uji Mann-Whitney U dan Wilcoxon Signed Rank digunakan untuk analisis pada level signifikansi 5%. Terdapat perubahan signifikan pada pengetahuan ibu setelah mendapat edukasi gizi. Perbedaan peningkatan skor pengetahuan ditunjukkan di antara kelompok intervensi (85,25+14,67) dan kelompok kontrol (72,98+14,67) dengan p=0,016, dan di antara pre-intervensi (59,99+8,60) dan post-intervensi (85,25+14,67) dengan p0,001. Namun, tidak ada perubahan signifikan terkait sikap dan praktik pemberian makan pada bayi dan anak. Pengetahuan ibu merupakan satu-satunya outcome yang dipengaruhi oleh intervensi edukasi gizi.